Hierarchy of labor motives of different professional groups of employees of medical institutions - A. V. Kukurika; E. I. Iurovskaia (Исследования и практика в медицине)
Improving the productivity, quality and availability of medical services directly depends on the effectiveness of motivational mechanisms for personnel management. Despite the sufficient empirical and practical experience in the field of health workforce management, data on the comparison of labor motivation among different professional categories of medical personnel are not often found. The article analyzes the main labor motives of nurses and doctors, reveals the differences in the motivational profiles of these categories of workers.Purpose of the study. Is to study and compare the motivation of doctors and nurses from budgetary healthcare institutions providing TB care to the population.Materials and methods. A sociological survey was conducted using a questionnaire form containing questions to study the labor motivation of healthcare workers. The study involved employees of various professional categories of public medical institutions – the Republican Clinical Tuberculosis Hospital and the Makeyevka Municipal TB Dispensary. Labor motives are structured into 3 blocks: material, socio-psychological and individual.Results. In the overwhelming majority, doctors and nursing staff of public health care institutions with a phthisiology profile are equally satisfied with the work they do. The most significant labor motives were identified for each category of medical personnel. For paramedical personnel, the factor of material motivation came out on top, but a convenient work schedule, relationships with superiors and a favorable psychoemotional climate made up the five most significant work motives. Physicians are more influenced by individual and socio-psychological motives: self-realization and professional interest are in the lead, remuneration, relationships with colleagues and patient care have a complex effect on the activities of doctors.Conclusion. This study confirms the principle of polymotivation of all categories of employees, therefore, the modernization of the motivational environment should be carried out taking into account group affiliation, individual characteristics, preferences and personal qualities of employees. Personnel-oriented system of motivation of medical personnel will solve most of the problems faced by the healthcare sector in today's changing market relations.